Deluxe Jim Crow : Civil Rights and American Health Policy, 1935-1954 - Thomas, Karen Kruse (Book collections on Project MUSE., 2011)
"Thomas provides a detailed history of federal health policy as it was applied to the U.S. South in the mid-twentieth century, a period when the region was described as "the number one health problem in the nation." In particular, she focuses on how reformers' early emphasis on across-the-board regional uplift was eclipsed by efforts to desegregate medical facilities and address racial disparities in the health care system"--